2019
DOI: 10.1002/glia.23694
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of cannabinoid signaling in microglia by adenosine A2A receptor antagonists

Abstract: Neuroprotective M2‐skewed microglia appear as promising to alter the course of neurodegenerative diseases and G protein‐coupled receptors (GPCRs) are potential targets to achieve such microglial polarization. A common feature of adenosine A2A (A2AR) and cannabinoid CB2 (CB2R) GPCRs in microglia is that their expression is upregulated in Alzheimer's disease (AD). On the one hand, CB2R seems a target for neuroprotection, delaying neurodegenerative processes like those associated to AD or Parkinson's diseases. A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 82 publications
0
49
0
3
Order By: Relevance
“…Interestingly, the induction of eCB-LTD is highly variable based on the stimulation paramaters and the brain region being examined, suggesting that there are multiple mechanistically distinct modes of eCB-LTD. More recent studies have even demonstrated astrocytic and microlical eCB signaling as a crucial regulators of synaptic plasticity, adding further complexity to the physiological role of eCBs (Franco et al, 2019;Navarrete and Araque, 2010;Navarrete et al, 2014).…”
Section: The Endocannabinoid Signaling Systemmentioning
confidence: 99%
“…Interestingly, the induction of eCB-LTD is highly variable based on the stimulation paramaters and the brain region being examined, suggesting that there are multiple mechanistically distinct modes of eCB-LTD. More recent studies have even demonstrated astrocytic and microlical eCB signaling as a crucial regulators of synaptic plasticity, adding further complexity to the physiological role of eCBs (Franco et al, 2019;Navarrete and Araque, 2010;Navarrete et al, 2014).…”
Section: The Endocannabinoid Signaling Systemmentioning
confidence: 99%
“…In mice, opposing functional interactions between A 2A Rs and CB 1 receptors in the hippocampus, as well as the Δ 9 -THC-induced cognitive impairment being blocked by an A 2A R antagonist, were demonstrated [ 131 ]. Such interactions might also occur in the microglia [ 132 ]; however, this must be confirmed in further studies.…”
Section: A 2a R and Behavioral Actions To Cocaimentioning
confidence: 99%
“…Этот факт означает, что ABHD12 является важнейшим фактором, регулирующим внеклеточный уровень 2-АГ и передачу сигналов CB рецепторам. Активность именно этой гидролазы может определять судьбу нейронного трансмиттерного сигнала [53,54] и «воспаленное» состояние микроглии [60] (рис. 1).…”
Section: Abhd12 -базовый фактор модулирующий количество доминирующегunclassified
“…Результаты, полученные в работах в последнее время, свидетельствуют о важном потенциале микроглиальных аденозиновых рецепторов в нейропротекции, поскольку они ослабляют воспаление и способствуют поляризации M2 [2,60]. Более того, установлено, что аденозиновый рецептор A2A находится в физическом контакте с каннабиноидным рецептором СВ2.…”
Section: Abhd12 -базовый фактор модулирующий количество доминирующегunclassified